A Multiple Mediational Meta-Analysis of the Influence of Proactive Personality on Subjective Career Success at the Career Exploration Stage. (May 2023) - Yu, Haibo; Dong, Zhenhua; Guan, Xiaoyu; Yan, Changli; Su, Xia; Cheng, Long
Drawing on the career construction theory model of adaptation, this meta-analytic structural equation modeling (MASEM) examines the effects of proactive personality on the subjective career success of adolescents and emerging adults. We identified 46 studies that covered 52 independent samples and 24, 092 participants through literature retrieval. Based on these studies, we created an integrative model linking proactive personality with career adaptability, student career construction, and subjective career success. The results of the meta-analysis showed that all bivariate relationships among proactive personality, career adaptability, student career construction, and subjective career success were significantly positive. The results of the MASEM indicated that career adaptability intervened in the relationship between proactive personality and subjective career success, but student career construction, as a suppressor, carried out the negative association between proactive personality, career adaptability and subjective career success in the sequence of adaptation. We also discuss the research implications and provide directions for future research.